Hemisection of a Mandibular Molar - Quader, SM Abdul; Alam, M Shamsul; Khan, M Osman Ghani; Moral, A Asgor (Update Dental College Journal, 2013)
Teeth once designated obsolete for rehabilitation and deemed for extraction should be re-evaluated for salvaging two thirds or even one third component of the individual teeth. Advances in dentistry, as well as the increased desire of patients to maintain their dentition, have lead to treatment of teeth that once would have been removed. In order to carry out this present day mandate, periodontally diseased teeth with severe bone loss and/or mandibular molar teeth exhibiting furcation invasions may well be retained by removal of one or more of their roots. This article describes a simple procedure for root amputation in mandibular molar and its subsequent restorations. DOI: http://dx.doi.org/10.3329/updcj.v1i1.13949 Update Dent. Coll. j: 2011; 1 (1): 18-22